Characterization of dry spells in Southeastern Brazil during the monsoon season. (29th January 2020) - Cunningham, Christopher
Abstract: Given the lack of studies about dry spells over Southeastern Brazil (SEB), the present study aims to characterize them considering their duration, geographical incidence, and association with rainfall. Uninterrupted sequences of no‐rain days were calculated using the high‐resolution (10 km) Multi‐Source Weighted‐Ensemble Precipitation data set (MSWEP; 1979–2016). The majority of dry spells (80%) last no more than 9 days and those remaining for 10 days or more are relatively rare (top 20%). January and February present a predisposition for the occurrence of dry spells, feature that is not observed in December. The life cycle of dry spells evolves in close association with the subseasonal rainfall tendency. When adding the perspective of dry spells, the effective peak of the monsoon season is December, the month with the highest rainfall rates and the lowest chances for dry spells. Afterward, dry spells modulate a progressive weakening of the rainy season until March, when a slight recovery may happen in the central northern portions of SEB. The relationship between dry spells and rainfall is not straightforward. For dry spells that are most common (up to 9 days), the most likely association is with negative monthly anomalies up to −1.0 SD . However, there are also significant chances of having dry spells associated with positive anomalies. Extreme long dry spells, but extremely rare as well, are unequivocally associated with negative anomalies. The geographic discrimination of dry spells evidences a dipole‐like feature, better seen in January and February, similar to the well‐known rainfall dipole. The north and northeast portions tend to be drier, more prone to the occurrence of dry spells, both short/frequent and long/infrequent. In the south and southwestern portions, dry spells tend to be shorter. The main result is the indication of a probable lessening in the rainy season, taking place between January and February that might affect a significant portion of SEB. Abstract : Dry spells are an important aspect of monsoonal rainfall regimes and may implicate significant impacts on agriculture. The present work has indicated the chance for a recurrent lessening in the rainy season due to increased dry spell activity. This break is most likely to take place between January and February and affects a significant portion of Southeastern Brazil. Common dry spells (up to 9 days) may incur monthly rainfall deficits of the order of 20 to 40%.